Modeling and Simulation of Logical Dual Ring ARCNET Train Communication Network - 巴全龙; 苟先太; 姚凤阳; 汤克 (机车电传动)
This paper built physical bus type logic ring communication network of train based on OPNET network simulation platform, which included network model, node model and process model. Based on this model, the simulation and optimization design had been done. The simulation results showed that the advantages of dual network redundancy, network delay time and the main factors , which influenced the end to end delay time.